2022
DOI: 10.1177/09603271211066586
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of long noncoding RNA APOA1-AS in the pathogenesis of preeclampsia

Abstract: Objective Long noncoding RNAs (lncRNAs) are involved in preeclampsia (PE), and apolipoprotein A-1 antisense RNA (APOA1-AS) and has been found to be associated with a number of diseases. Our study aims to understand the involvement of APOA1-AS in PE. Methods Clinically, APOA1-AS expression in early-onset severe PE (EOSPE) patients and healthy controls was detected by real-time quantitative polymerase chain reaction. In vitro experiments were divided into control [coculturing trophoblasts with human uterine micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…It has been reported that the expression of APOA1 was high in the blood and maternal-fetal interface during early miscarriages [17]. Additionally, evidence has revealed that apolipoprotein A-1 antisense RNA was increased in the placental tissues of early onset severe PE, and downregulation of APOA1-AS protected against TNFα-induced inhibition of trophoblast integration into endothelial networks, thus exerting protective effects against PE in rats [12]. This evidence indicates that the upregulation of APOA1 might indicate adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that the expression of APOA1 was high in the blood and maternal-fetal interface during early miscarriages [17]. Additionally, evidence has revealed that apolipoprotein A-1 antisense RNA was increased in the placental tissues of early onset severe PE, and downregulation of APOA1-AS protected against TNFα-induced inhibition of trophoblast integration into endothelial networks, thus exerting protective effects against PE in rats [12]. This evidence indicates that the upregulation of APOA1 might indicate adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Apolipoprotein A1 (APOA1) is a major apoprotein constituent of high-density lipoproteins that plays important roles in tumor invasion and metastasis [10,11]. It has been reported that increased lncRNA APOA1-AS was found in the placental tissues of early onset severe PE, and downregulation of APOA1-AS protected against TNF-α-induced inhibition of trophoblast integration into endothelial networks, thus exerting protective effects in PE rats [12]. Recent findings have revealed the crucial roles of APOA1 in inflammation, tumor growth, angiogenesis, invasion, and metastasis [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent protein interaction analysis showed that APOA1 was the key protein of DFU. It is believed that APOA1 may affect local coagulation, in ammation, angiogenesis, and wound repair [33][34][35].…”
Section: Discussionmentioning
confidence: 99%